Analyses of Bacterial Community Dynamics Present in Culex quinquefasciatus Collected from Tamil Nadu, India - A Metagenomic Approach: Analyses of Bacterial Community Dynamics Present in Culex quinquefasciatus Collected from Tamil Nadu, India - A Metagenomic Approach - Singh, J. Rajesh (International Journal of Pharmaceutical & Biological Archive, 2018)
Culex quinquefasciatus are among the most important vectors of arboviral diseases worldwide. Recent studies indicate that diverse midgut microbiota of mosquitoes significantly affects development, digestion, metabolism, and immunity of their hosts. Here, we studied the bacterial diversity found in midgut part of C. quinquefasciatus to understand the host and microbe interaction. The adult C. quinquefasciatus mosquitos were collected from Loyola College Campus, Chennai, using ovitraps, and midgut part was extracted; moreover, the DNA templates were isolated and amplified by polymerase chain reaction. The DNA amplicons were sequenced by Illumina MiSeq gene sequencer. The total of 279,157 reads was classified into 85, the bacterial genera of Pseudomonas, Klebsiella, Staphylococcus, and Aeromonas predominantly found to be high when compared to the other bacterial genera. The present data strongly encourage further investigations to verify the potential role of the detected bacteria in mosquito for the transmission of several vectoral diseases.